Model Order Reduction for Magneto-Quasistatic Equations. Issue 1 (2015) - Kerler, Johanna; Stykel, Tatjana
Abstract: We consider model reduction of Maxwell's equations arising in magneto-quasistatic problems. A finite element discretization of such equations leads to large-scale differential- algebraic equations of special structure. For model reduction of linear systems, we employ a balanced truncation approach, whereas nonlinear systems are reduced using a proper orthogonal decomposition method combined with a discrete empirical interpolation technique. We will exploit the special structure of the underlying problem to improve the performance of the model reduction algorithms.